Do Strong Work Ethics Always Improve Performance? The Hidden Role of Corruption Intention in Family-Owned Businesses Company - Tan Evan Tandiyono; Ida Aju Brahmasari; Siti Mujanah (DINASTI RESEARCH, 2026)
This study investigates the influence of subjective well-being, self-esteem, and social exchange on employee performance within family-owned businesses (FOBs) in the Gerbang Kertosusila region. Unlike traditional family firms, the FOBs in this study are characterized by family members acting solely as shareholders, while operational management is delegated to external professionals and relatives. Using a quantitative causal-explanatory approach, data was collected from 308 employees across 10 family-owned companies and analyzed using Structural Equation Modeling (SEM) with AMOS 26. The findings reveal that subjective well-being, self-esteem, and social exchange each have a significant positive effect on employee performance. These results highlight the importance of psychological and relational factors in enhancing the productivity of employees within family-owned enterprises. By emphasizing emotional well-being, individual self-worth, and mutual workplace relationships, this study provides valuable insights for FOB leaders in fostering a high-performing organizational culture supported by strong internal social dynamics.